Strategic Factors in the Capital Structure of the Services and Communication Sectors in Mexico - Gaytán Cortés, Juan; Bonales Valencia, Joel; Vargas Barraza, Juan Antonio (Mercados y Negocios, 2016)
The purpose of this research was to identify the strategic factors of the country and the companies, to incorporate long term debt in the capital structure of the companies of services and the communication sector that they quoted on the Mexican Stock Exchange in the periods 2000-2012. The mathematical model and the factors used in this empirical study were used in the investigations that were analyzed in the theoretical framework.